Harmful microalgae assemblage in the aquaculture area of Aman Island, Northen Strait of Malacca - Roziawati, Mohd Razali; Chui, Pin Leaw; Hong, Chang Lim; Lee, Nyanti; Ismail, Ishak; Po, Teen Lim (Malaysian Abstracting and Indexing System, 2015)
A field survey was carried out in Aman Island, the northern Strait of Malacca, to investigate the occurrence of harmful microalgae. The area is known for marine finfish cage-culture and blood cockle farming. Plankton samples were collected fortnightly between July 2011 and September 2013. A total of 58 phytoplankton genera were recorded; 37 belong to the diatoms, and 21 genera were dinoflagellates. Harmful microalgae species were identified microscopically, of which nine are bloom-forming species that responsible for fish kills. These included Akashiwo sanguinea, Chaetoceros affinis, Cha. curvisetus, Cha. laevis, Ceratium furca, C. fusus, Cochlodinium sp., Karlodinium australe and Noctiluca scintillans. Three Alexandrium species were identified from the samples, i.e. A. leei, A. affine and Alexandrium sp. Pulau Aman; some species in the genus have been known to associate with Paralytic Shellfish Poisoning (PSP). Diarrhetic Shellfish Poisoning (DSP)-toxin producers were also encountered in the water samples, viz. Dinophysis acuminata, D. caudata, Dinophysis sp. and Prorocentrum micans. The harmful diatom, Pseudo-nitzschia spp. that associated with Amnesic Shellfish Poisoning (ASP), was commonly found in the water samples. Cell abundance of each harmful microalga was enumerated. The results showed that cell densities of harmful microalgae were relatively low throughout the sampling period. The microalgae community was dominated by Ceratium furca in May 2012, with cell densities exceeding 70,000 cells L-1; no fish kill event was reported during the time. Even though no fish kill or shellfish poisoning was reported in the area, he presence of harmful microalgae albeit at low cell densities, may pose a potential threat to human health and seafood biosecurity. Therefore, regular phytoplankton monitoring is necessary to safeguard human health and seafood industries in the country.